Riga-Fede disease: report of a case in an infant - Hubka, Joanna; Grużewska-Piotrowska, Kinga; Grużewska, Agnieszka; Pająk, Monika; Wcisło, Wojciech (Journal of Education, Health and Sport, 2023)
Riga-Fede disease (RFD) is a rare, benign condition found in infants, characterized by ulcers in the oral mucosa, around the tongue and gums. It is caused by repeated injuries, caused by movements of the tongue over the lower incisors. It usually coexists with neonatal teeth. Although it starts as a small ulcer, it can progress to a large fibrous lesion. Symptoms include pain, swelling and difficulty swallowing and sucking. Early diagnosis and treatment are important to prevent late complications, including insufficient food intake, growth retardation and deformity of the tongue, gums, lips and floor of the mouth. The diagnosis is usually made on the basis of medical history and clinical features. The following paper presents the case of a 9-month-old boy with a lump occurring in the fundus of the mouth, at the base of the tongue.